Structure of HIV-1 Vpr in complex with the human nucleotide excision repair protein hHR23A - In-Ja L. Byeon (Nature Portfolio, 2021)
Vpr is a HIV-1 accessory virulence factor that also interacts with the human DNA repair protein hHR23A. Here, the authors present the structure of Vpr in complex with the C-terminal half of hHR23A comprising the XPC-binding and ubiquitin-associated domains, which reveals that hHR23A interacts with the DCAF1-binding and not the substrate-binding Vpr surface and further illustrates how Vpr acts as a versatile structural adapter that targets diverse DNA repair pathways.